Dysregulation of hepatic microRNA expression profiles with Clonorchis sinensis infection - Han, Su (BMC Infect Dis, 2016)
BACKGROUND: Clonorchiasis remains an important zoonotic parasitic disease worldwide. The molecular mechanisms of host-parasite interaction are not fully understood. Non-coding microRNAs (miRNAs) are considered to be key regulators in parasitic diseases. The regulation of miRNAs and host micro-environment may be involved in clonorchiasis, and require further investigation. METHODS: MiRNA microarray technology and bioinformatic analysis were used to investigate the regulatory mechanisms of host miRNA and to compare miRNA expression profiles in the liver tissues of control and Clonorchis sinensis (C. sinensis)-infected rats. RESULTS: A total of eight miRNAs were downregulated and two were upregulated, which showed differentially altered expression profiles in the liver tissue of C. sinensis-infected rats. Further analysis of the differentially expressed miRNAs revealed that many important signal pathways were triggered after infection with C. sinensis, which were related to clonorchiasis pathogenesis, such as cell apoptosis and inflammation, as well as genes involved in signal transduction mechanisms, such as pathways in cancer and the Wnt and Mitogen-activated protein kinases (MAPK) signaling pathways. CONCLUSIONS: The present study revealed that the miRNA expression profiles of the host were changed by C. sinensis infection. This dysregulation in miRNA expression may contribute to the etiology and pathophysiology of clonorchiasis. These results also provide new insights into the regulatory mechanisms of miRNAs in clonorchiasis, which may present potential targets for future C. sinensis control strategies.